2020
DOI: 10.3390/cancers12061634
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestations and Complications in Childhood Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a heterogeneous group of diseases, whose classification is based on lineage-commitment and genetics. Although rare in childhood, it is the most common type of acute leukemia in adults, accounting for 80% of all cases in this age group. The prognosis of this disease remains poor (especially in childhood, as compared to acute lymphoblastic leukemia); however, overall survival has significantly improved over the past 30 years. The health of the oral cavity is a remarkable reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 46 publications
(136 reference statements)
1
51
0
Order By: Relevance
“…It is well known that poor hygiene can exacerbate gingival growth due to endotoxins released by pathogenic bacteria that elevate the levels of inflammatory cytokines. 15 Shankarapillai et al 20 reported that gingival growth was observed in three quarters of AML patients, probably associated with poor hygiene. Similarly, oral bleeding associated with poor hygiene that frequently occurs in the gingiva has been previously described in 15 patients with AML and ALL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that poor hygiene can exacerbate gingival growth due to endotoxins released by pathogenic bacteria that elevate the levels of inflammatory cytokines. 15 Shankarapillai et al 20 reported that gingival growth was observed in three quarters of AML patients, probably associated with poor hygiene. Similarly, oral bleeding associated with poor hygiene that frequently occurs in the gingiva has been previously described in 15 patients with AML and ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The acute form is abrupt and aggressive with primitive blasts cells in the peripheral blood and activation of mechanisms of tissue infiltration, while the chronic form is linked to a prolonged course and the presence of more mature cells. 11,15 Nevertheless, both may occur in the myeloid and lymphoid lineage and demographic differences among affected individuals have been observed. 15 Acute leukaemia usually affects children or young adults, 15 as also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute myelogenous leukemia (AML) is a common pediatric hematologic cancer in children younger than 15 years ( 1 , 2 ). In the past several years, the survival rate for AML has increased because of the improvement of therapeutic strategies, risk stratification, and supportive care ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%